Production of poplar containerized plants : differences in cutting types and fertilization regimes - Fransson, Thomas (SLU/Southern Swedish Forest Research Centre, 2016)
Populus is one of the most economically important genuses in the world’s temperate zones. They are known for their fast growth, easy propagation, many usages, aesthetic values and propensity to hybridize. Planting stock for poplar is usually divided into rooted and unrooted material. Unrooted can be divided into cuttings (2- 100 cm) and whips (1,5 to 6 m). Rooted can be divided into bare-rooted and containerized plants. The goals of this study were to investigate; (1) how different cutting types influenced survival and plant growth of containerized plants. (2) how fertilizer regimes influenced plants growth response to cutting types. The experiment consisted of 72 treatment combinations: eight cutting types, three clones (Rochester, Clone 15 and OP42), and three fertilizing treatments (a standard NPK solution, an amino acid solution and unfertilized control). 15 blocks, 1080 plants in total, were established in a greenhouse and grew for teen weeks before harvest. Over all clones, treatments and cuttings, the survival rate was 79 %. Our results revealed that cutting type influenced height, diameter, biomass production and survival especially if plants were not fertilized. Fertilization lowered these differences although they were still present after fertilization. Plant growth (clones and cutting types) increased if fertilizer NPK or arGrow were used with NPK fertilization increasing plant growth the most. Plants fertilized with arGrow had a higher root to shoot ratio.